The relevance of financial information in the valuation of the share price of Chile and Mexico - Vásquez Quevedo, Noemí; García Ramírez, Diego Armando (Estudios de Administración, 2012)
This paper analyzes the value relevance of financial information, measured by the coefficient of determination (R2), relevance being higher for Chilean companies than for Mexican ones in most of the period analyzed. We employed the Ohlson model (1995), with accounting variables such as earnings per share and book value as well as the share price for both Chilean and Mexican companies listed on the Santiago Stock Exchange, the Mexican Stock Exchange, and also some of those companies are listed as well in the U.S. stock exchange during the period 1992-2010. Additionally, tests were performed to classified companies according to their main thrust: tangible and intangible. We also obtained results for the data on companies cross listed on both U.S. stock exchange and their local stock exchange, and performed a cross analysis in terms of their economic endeavor as well. The results obtained on panel data show that the accounting variables are significant to determine the share price in both the local stock exchange and the U.S. stock exchange. These results are consistent in classifying firms in tangible and intangible, and for the most representative economic endeavor of each country.